Fourteen new species of Heterospilus Haliday (Hymenoptera, Braconidae: Doryctinae) from Brazil - Chiletto, Bo.; Penteado-Dias, Am. (Zootaxa, 2016)
Fourteen new species of the genus Heterospilus Haliday found in semideciduous mesophilic forest areas at São Paulo State, Brazil are described. They are: Heterospilus ayewai sp. n., H. caetetus sp. n., H. fernandesi sp. n., H. fiorelinii sp. n., H. granulosus sp. n., H. homalos sp. n., H. intervalesi sp. n., H. japi sp.n., H. meloi sp. n., H. mesopleuron sp. n., H. periotoi sp. n., H. riveroni sp. n., H. sormusi sp. n., and H. virginensis sp. n. Heterospilus species are characterized by the sculpturation of the vertex: granulate, striate, rugose, or smooth, without sculpturation. All specimens of Heterospilus in this study are in the species group with a smooth, unsculptured vertex.